How does Emotional Intelligence Impact Employee Performance? Validation of WEIP-S among Indian Professionals - JAIN, DR.SHILPA; BAJAJ, DR.BHAVNA (The journal of contemporary issues in business and government, 2021)
Emotional Intelligence has been linked with many desirable performance outcomes, however the strength and nature of this impact has often been debated. Leading researchers advocate the use of specific, relevant and well established instruments in empirical research to study Emotional Intelligence at the workplace. To this end, the current work validates WEIP-S, a popular Emotional Intelligence measure which has been specifically tailored for use in organizational research for use among Indian respondents. Results of study 1 ( n = 253) and study 2 ( n=852 ) suggest that WEIP-S retains its original four factor structure and shows acceptable reliability when tested among working professionals from diverse economic sectors in India. Results of study 3 ( n=324) provide evidence for significant positive impact of Emotional Intelligence at the workplace, by linking WEIP-S scores to supervisor evaluations of performance. Additionally, results clarify the differential impact of the four dimensions of Emotional Intelligence on various aspects of employee performance.